THE EFFECT OF IRON OXIDE AND POLYCARBOXYLIC ACIDS ON THE PHOTODEGRADATION OF 2,6-DIMETHYPHENOL (Sciences & Technology. A, exactes sciences, 2014)
A natural iron oxide (NIO) was applied for the photodegradation of 2,6-dimethylphenol in presence of polycarboxylic acids under UV irradiation. The dependence of 2,6-DMP degradation was attributable to the formation of dissolved Fe–polycarboxylate in the solution and adsorbed on the surface of natural iron oxide. The results showed that the photodegradation of 2,6-DMP could be enhanced greatly in the presence of oxalate. The variables studied were the aqueous pH, the presence of hydrogen peroxide and temperature in NIO / oxalate / UV system. The optimal pH value was found to be in the range of 3–4. It was found that the formation of Fe (II) in NIO / oxalate system occurred more vigorously at the initial stage and gradually became moderate. Furthermore, the formation of H2O2 during the photoreaction was studied to explore its relationship with the photodegradation efficiency and the iron cycling process. The use of 2.0% of isopropanol as a scavenger confirmed the intervention of hydroxyl radicals in the degradation of 2,6-DMP.